What Determines the Value of Company? Study on the Consumer Non-Cyclicals Sector on IDX in 2020-2022 - Kumalasari, Putu Diah; Endiana, I Dewa Made (First Ciera Publisher, 2024)
Companies that demonstrate strong performance and achieve maximum profitability are poised to witness a surge in demand for their shares, consequently leading to elevated share prices. These high share prices are indicative of the augmented value of the company. This research aims to investigate the impact of profitability, liquidity, investment decisions, dividend policy, and sales growth on company value. The study comprises 29 companies operating in the consumer non-cyclicals sector, listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. The analytical method employed encompasses multiple linear regression analysis. The findings reveal that profitability, liquidity, investment decisions, and sales growth exert a positive influence on company value. Conversely, dividend policy is shown to have no discernible effect on company value. Additionally, the study suggests the incorporation of further independent variables in future research, particularly focusing on factors such as Good Corporate Governance (GCG) and cash holding, which are anticipated to exert a substantial impact on company value.